2014
DOI: 10.3109/14397595.2014.891495
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clinical parameters associated with serum oxidative stress in patients with rheumatoid arthritis

Abstract: The serum level of ROM was associated with CRP and DAS28-ESR, suggesting that ROM, in conjunction with CRP and MMP3, may be able to be used as a new biological disease marker to evaluate the disease activity of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 27 publications
0
44
1
2
Order By: Relevance
“…In our study, patients were prospectively followed, and patients with comorbid diabetes mellitus, chronic kidney disease more than grade 3, and chronic obstructive pulmonary disease (COPD) were excluded, because these comorbidities permanently and endogenously upregulate oxidative stress markers. Therefore, our study may provide better evidence than previous reports [8] [9].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In our study, patients were prospectively followed, and patients with comorbid diabetes mellitus, chronic kidney disease more than grade 3, and chronic obstructive pulmonary disease (COPD) were excluded, because these comorbidities permanently and endogenously upregulate oxidative stress markers. Therefore, our study may provide better evidence than previous reports [8] [9].…”
Section: Discussioncontrasting
confidence: 54%
“…A simple test for d-reactive oxygen metabolites (d-ROM) has been developed and is able to detect the total amount of ROS in the body [7]. Previous reports demonstrated that d-ROM values in RA patients were significantly higher than those in osteoarthritis patients [8], and that d-ROM levels are significantly correlated with disease activity in RA [9].…”
Section: Introductionmentioning
confidence: 99%
“…31) Blood d-ROMs level increases in diseases with enhanced oxidative stress, and decreases by treatment that reduces oxidative stress. 32,33) Regarding the effect of resveratrol on oxidative stress, a report has shown that resveratrol treatment decreases ROS production induced by TNF-α or NF-κB in human vascular endothelial cells. 34) Oxidative stress is known to be elevated in diabetic conditions through the generation of advanced glycation end products (AGEs) and activation of NADPH oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…[34] Different mechanism may explain the efficacy of D-002 in this model, but obviously since it has been shown anti-inflammatory action [16 -20, 23, 24] and the ability to inhibit COX and 5-LOX enzymes [21,22] should be one of the mechanism that support the effects here seen, at least partially. Taking into account that the increase of oxidative stress has been linked with the development of RA and that some antioxidants have demonstrated efficacy in RA model, [35][36][37][38] we can hypothesize that the antioxidant effects of D-002 could have contributed to the present results, preferred hypothesis. Nevertheless, our study was not focused on the mechanisms whereby D-002 may be effective, but on elucidating whether its oral administration is able to reduce the distinctive histopathological lesions in this model of RA, as demonstrated.…”
Section: International Journal Of Pharmacology Phytochemistry and Etmentioning
confidence: 77%